The Role of Training and Development, Work Achievement and Educational Background on Career Development of Employees at PT Pos Persero - Ni Luh Kardini; Suparman; Robiansyah; Roy Setiawan; Erni Yuningsih (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study's goal is to recognize and assess how employee career growth is impacted by work performance, education, training, and experience. 87 employees who participated in the study and received questionnaires received primary data collection. Both the convenience sampling approach and the non-probability sampling method were used for the sampling. The study of this paper employs a number of linear regression tests. The results of the study show that job performance and work experience have a significant impact on an employee's career development partially or concurrently, whereas education and training only have a simultaneous impact. These results demonstrate that the dependent variable, with a coefficient of determination of 0.648, has a value of 64.8% in explaining employee career progression when the components of job performance, education and training, and work experience are combined.